Anthelmintic Activity of Castor Oil and Mustard Oil - Sravanthi, Srilakshmi Sidagonde, Sarvani Manthri*, Kota Chaitanya (Journal of Phytology, 2011)
The aim of the present study was to investigate the anthelminthic activity of vegetable fixed oils, castor oil and mustard oil using adult earthworm, Pheritima posthuma. The oils were tested at different concentrations for the determination of paralysis time and death time of the earthworms. Albendazole is used as standard and it was found that castor oil and mustard oil showed a better anthelminthic activity in comparison with the standard. Key words: Anthelminthic activity, Albendazole, Earthworm, Castor oil, Mustard oil <span style="font-weight: normal; font-size: 7pt; line-height: 110%; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-variant: normal! important; mso-fareast-language: EN-SG; mso-font-kerning: 0pt; mso-no-proof: no; mso-ansi-language: EN-SG;" lang="EN-SG">Sarvani Manthri et al. Anthelmintic Activity of Castor Oil and Mustard Oil. J Phytol 3/3 (2011) 12-14.